IFPRI strategy 2026-2030: Food policy research for a changing world - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
IFPRI’s Strategy for 2026–2030 reaffirms the Institute’s commitment to providing research-based policy solutions. IFPRI works with partners to use the power of policy to improve food security, nutrition, and livelihoods, contribute to empowerment, and promote sustainability and climate resilience, particularly in low- and middle-income countries. This new strategy responds to the many challenges and opportunities emerging today, from climate change to growing inequities to digital technologies and more. It combines a proven four-pronged research and engagement approach with five research themes that reflect a systems understanding of food policies—from farm to consumer. IFPRI’s research is designed to support impact at scale through country- and region-led policies that will help to sustainably end poverty, hunger, and malnutrition.